Translation Techniques on Official Soundtrack of Moana Film's Song - Angela Sherine Findi Kurnia Citra; Jumanto Jumanto (International Forum of Researchers and Lecturers, 2023)
This research is entitled Translation Techniques on Official Soundtrack of Moana Film’s Song. This research was aimed at identifying translation techniques in Official Soundtrack of Moana Film “How Far I’ll Go” Song in Indonesian Version. This research used a qualitative method to analayze the translation techniques in the Official Soundtrack of Moana Film “How Far I’ll Go” Song in Indonesian Version. There were some steps in analysing the existing data. The first step was selecting the data, the second was identifying the data, the third was classifying the data, the fourth was analyzing the data, and the last was making conclusions and suggestions. Based on the analysis, the writer concluded that there were 6 translation techniques used in OST Moana: How Far I’ll Go. According to the data, the researcher found 32 data containing several translation techniques, namely: 1 (3,13%) data with amplification technique; 1 (3,13 %) data with Literal Translation technique; 6 (18,75%) data with discursive creation technique; 1 (3,13%) data with Particularization technique; 7 (21,88%) data with reduction technique; and 16 (50%) data with Established Equivalence technique. According to the results of analysis, the dominant type of translation technique is Established Equivalence. It has the highest frequency of the data, as there were 16 data (50%). This technique used terms or expressions that were recognized as equivalents in the target language. It was used for describing the same situations through different stylistic or structural expressions. The translator translated the utterances from the source language into the target language using the established equivalence technique since the translator used terms or words that were more familiar in the target language, so the message could be well delivered to the target language.